2023
DOI: 10.1093/nar/gkad672
|View full text |Cite
|
Sign up to set email alerts
|

TeloBase: a community-curated database of telomere sequences across the tree of life

Martin Lyčka,
Michal Bubeník,
Michal Závodník
et al.

Abstract: Discoveries over the recent decade have demonstrated the unexpected diversity of telomere DNA motifs in nature. However, currently available resources, ‘Telomerase database’ and ‘Plant rDNA database’, contain just fragments of all relevant literature published over decades of telomere research as they have a different primary focus and limited updates. To fill this gap, we gathered data about telomere DNA sequences from a thorough literature screen as well as by analysing publicly available NGS data, and we cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To verify the completeness of our genome chromosome assembly, we conducted an analysis of telomere repeat sequences on each chromosome based on the genome repeat sequence annotation results. Initially, we analyzed the telomere repeat motif sequences of Lepidoptera insects in TeloBase 58 , and we found that the majority of repeat motifs ranged from 5 to 9 bp in length, and (TTAGG)n/(CCTAA)n is the main motif in telomeres. After that, we identified regions within 15 kb at both ends of the chromosomes in our results where the length of repeat sequences exceeded 1k,and the repeat motif sequence ranged from 5 to 9 bp.…”
Section: Technical Validationmentioning
confidence: 99%
“…To verify the completeness of our genome chromosome assembly, we conducted an analysis of telomere repeat sequences on each chromosome based on the genome repeat sequence annotation results. Initially, we analyzed the telomere repeat motif sequences of Lepidoptera insects in TeloBase 58 , and we found that the majority of repeat motifs ranged from 5 to 9 bp in length, and (TTAGG)n/(CCTAA)n is the main motif in telomeres. After that, we identified regions within 15 kb at both ends of the chromosomes in our results where the length of repeat sequences exceeded 1k,and the repeat motif sequence ranged from 5 to 9 bp.…”
Section: Technical Validationmentioning
confidence: 99%
“…Evaluation of WGS data through the TeloBase database [27] indicated that C. purpureus harbors the canonical plant-like telomere repeat, TTTAGGG. We analyzed TL in four natural isolates of C. purpureus collected from three different geographical locations: R40 (male strain, New York, USA), GG1 (female strain, Austria), B150 and B190 (female and male lines, respectively, Alaska, USA).…”
Section: Telomere Length Analysis In Dioecious Bryophyte Speciesmentioning
confidence: 99%
“…Unlike the situation with the flowering plants [27,28], very few bryophyte species have previously been investigated for specific features of telomere biology. All bryophytes analyzed so far harbor the canonical Arabidopsis-type telomere repeats TTTAGGG [29][30][31][32], and in a few species, the composition of telomeric repeats can be deciphered from the whole-genome sequencing data [18,20,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres are nucleoprotein complexes located at chromosome ends [1]. In most eukaryotes, the telomere contains simple repetitive sequences, such as (TTAGGG) n in vertebrates, with the G-rich strand going 5 ′ to 3 ′ toward the chromosome end [2,3]. Although most parts of the telomere are double-stranded, the very end of the telomere has a single-stranded 3 ′ overhang [4,5].…”
Section: The Telomere Structure and Telomere Functionsmentioning
confidence: 99%